Accessing Early Intervention for Psychosis Services in New Zealand – The Light at the End of the Tunnel - Rebecca E Grattan; Gloria Fraser; Megwyn A R Wolmarans; Amanda Clifford (Community Mental Health Journal, 2026)
Abstract Early intervention for psychosis (EIP) has significantly improved outcomes for young people experiencing early psychosis. However, access to services is often variable, and can be impacted by wider systemic factors such as poverty and systemic racism, alongside the design of the wider mental health system. This study took a critical realist perspective examining participant journeys to accessing early psychosis care in New Zealand. Nineteen service users and four family members from three early psychosis services across New Zealand were interviewed. Findings were analysed using reflexive thematic analysis. Four themes were identified. “Something is wrong, but we don’t know what” describes initial difficulties identifying emerging psychosis symptoms, not only for the participants and their families, but also for health care professionals. “An unfriendly mental health system” highlights difficulties finding mental health support. “Early psychosis services, the light at the end of the tunnel” encapsulates participants’ overwhelmingly positive experiences in EIP services, right from initial contact. Finally, family and whānau (wider family and community) supports were identified as key for participants. Participants were impacted by the sociocultural setting of New Zealand early psychosis services, with lack of knowledge of psychosis alongside traumatic inpatient experiences being key barriers to accessing care. While EIP services were experienced positively, there was a lack of support for families evident and accessing services was often difficult.